Rapid, inexpensive fabrication of electrophoretic microdevices for fluorescence detection. Issue 16 (8th July 2022) - Nelson, Daniel A.; Thompson, Brandon L.; Scott, An‐Chi; Nouwairi, Renna; Birch, Christopher; DuVall, Jacquelyn A.; Roux, Delphine Le; Li, Jingyi; Root, Brian E.; Landers, James P.
Abstract: The laser print, cut, and laminate (PCL) method for microfluidic device fabrication can be leveraged for rapid and inexpensive prototyping of electrophoretic microchips useful for optimizing separation conditions. The rapid prototyping capability allows the evaluation of fluidic architecture, applied fields, reagent concentrations, and sieving matrix, all within the context of using fluorescence‐compatible substrates. Cyclic olefin copolymer and toner‐coated polyethylene terephthalate (tPeT) were utilized with the PCL technique and bonding methods optimized to improve device durability during electrophoresis. A series of separation channel designs and centrifugation conditions that provided successful loading of sieving polymer in less than 3 min was described. Separation of a 400‐base DNA sizing ladder provided calculated base resolution between 3 and 4 bases, a greater than 18‐fold improvement over separations on similar substrates. Finally, the accuracy and precision capabilities of these devices were demonstrated by separating and sizing DNA fragments of 147 and 167 bases as 148.62 ± 2 and 166.48 ± 3 bases, respectively.